2008
DOI: 10.1186/1471-2180-8-163
|View full text |Cite
|
Sign up to set email alerts
|

Development of a loop-mediated isothermal amplification assay for sensitive and rapid detection of Vibrio parahaemolyticus

Abstract: Background: Vibrio parahaemolyticus is a marine seafood-borne pathogen causing gastrointestinal disorders in humans. Thermostable direct hemolysin (TDH) and TDH-related hemolysin (TRH) are known as major virulence determinants of V. parahaemolyticus. Most V. parahaemolyticus isolates from the environment do not produce TDH or TRH. Total V. parahaemolyticus has been used as an indicator for control of seafood contamination toward prevention of infection. Detection of total V. parahaemolyticus using conventional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
100
1
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 136 publications
(112 citation statements)
references
References 14 publications
8
100
1
1
Order By: Relevance
“…The LAMP reaction was performed as described previously [Hill et al, 2008;Yamazaki et al, 2008]. Each reaction mixture (total volume of 25 μL) contained 10× Bst ThermoPol buffer 2.5 μL, MgCl 2 (25 mmol/L) 3 μL, dNTP's (each 2.5 mmol/L) 3 μL, betaine (5 mol/L) 2 μL, inner primers (40 μmol/L) of each 1 μL, outer primers (10 μmol/L) of each 1 μL, loop primer (10 μmol/L) of each 1 μL, Bst DNA polymerase (New England Biolabs, Inc., Ipswich, MA) large fragment 1 μL (8units), DNA template 2 μL, and ddH 2 O×5.5μL.…”
Section: Lamp Primers and Analysis Of Lamp Productsmentioning
confidence: 99%
“…The LAMP reaction was performed as described previously [Hill et al, 2008;Yamazaki et al, 2008]. Each reaction mixture (total volume of 25 μL) contained 10× Bst ThermoPol buffer 2.5 μL, MgCl 2 (25 mmol/L) 3 μL, dNTP's (each 2.5 mmol/L) 3 μL, betaine (5 mol/L) 2 μL, inner primers (40 μmol/L) of each 1 μL, outer primers (10 μmol/L) of each 1 μL, loop primer (10 μmol/L) of each 1 μL, Bst DNA polymerase (New England Biolabs, Inc., Ipswich, MA) large fragment 1 μL (8units), DNA template 2 μL, and ddH 2 O×5.5μL.…”
Section: Lamp Primers and Analysis Of Lamp Productsmentioning
confidence: 99%
“…The increase in the turbidity of the reaction mixture due to the production of the white precipitate correlates with the amount of DNA synthesized (6, 7, 13). Thus, LAMP assays do not require expensive equipment and are highly precise (3,18,19).Here we describe a rapid and simple LAMP assay for detection of the tdh, trh1, and trh2 genes of V. parahaemolyticus. We also determined the sensitivity of this LAMP assay using spiked shrimp samples.…”
mentioning
confidence: 99%
“…The increase in the turbidity of the reaction mixture due to the production of the white precipitate correlates with the amount of DNA synthesized (6, 7, 13). Thus, LAMP assays do not require expensive equipment and are highly precise (3,18,19).…”
mentioning
confidence: 99%
“…Previous studies have reported the sensitivity of the LAMP method ranges from 10 2 to 10 5 colony forming unit (CFU)/g V. parahaemolyticus in spiked oysters. 17,19) However, seafood with low levels of V. parahaemolyticus has potential risks to human infection because a small number of this pathogen, e.g., ca. 10 2 cells/g seafood, can increase substantially, e.g., >10…”
Section: 7)mentioning
confidence: 99%
“…Therefore, it may be appropriate to target tlh/ldh gene for the detection of V. parahaemolyticus. 11,[15][16][17] The loop-mediated isothermal amplification (LAMP) method described by Notomi et al is more advantageous than the PCR assay because it is more rapid, easier to perform and does not necessarily require expensive thermal cycler machine. 18) In the LAMP method it is possible to amplify DNA fragments within 90 min by using only water bath or heat block.…”
mentioning
confidence: 99%